Poesia oral tradicional e funcionalidade - Nogueira, Carlos; Silva-Semik, Véronique Le Dü da (Trabalhos de Antropologia e Etnologia, 2020)
Oral poetry cannot be understood outside of the social structure in which they live, nor the functioning of the community can be fully understood without a knowledge of its oral poetry. Therefore, in this study, influenced by Paul Zumthor’s thought, we try to demonstrate that a serious approach to oral poetry cannot fix solely in the literary, nor only in its cultural, anthropological and sociological context. The oral poetry, as the traditions in general, only exists because it fulfills functions. Reflecting on this aspect is also thinking about the social and cultural context of literary performance, the idiosyncrasy of the poet-performers and the social group, the species, the language and style, the circumstances of the composition, transmission and reception of texts.